Informed consent dalam kajian hukum pidana di bagian bedah RS DR Sardjito tahun 1996-1997 - Susi Hadidjah dan Suhartini (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Informed consent in medicine is the approval of the patient of a certain medical measure after receiving complete information about the medical measure. In the execution the doctor may find another disease which needs necessarilly prompt measure, giving no opportunity to obtain family's approval. This may result in a patient's or family's suit against the doctor or hospital taking care of the patient. Objectives: This study was carried out to know whether there were any medical treatments conducted without informed consent. Method: This research is retrospective: data were taken from patients in Sardjito Hospital operated in Surgery Department in the years 1996 and 1997. Result and conclusion: The subjects were 200 patients, consisting of 65,5% female and 34,5% male patients. Percentage of patients aged under 20 years was 22,5%, 20 — 40 years 57,5% and older than 40 years 20%. Patient origin: 65,5% from Daerah istimewa Yogyakarta (Special Territory of Yogyakarta) and 34,5% outside of Yogyakarta. Major surgical cases contributed 57% and minor surgical cases 43% to all surgeries. Categories of the surgical measures: emergency 2% and elective 98%. informed consents signed by patient or family numbered 199 (99,5%). Only 1 (0,5%) was not signed because the patient was not hospitalized. Keywords: informed consent, surgical measure, emergency, elective